2006
DOI: 10.3148/67.2.2006.67
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers’ Dietary Behaviours:Parents’ Perspectives

Abstract: Purpose-Preschoolers' dietary intake behaviours are described from the perspective of their parents.Methods-A maximum variation sample of 71 parents of preschoolers participated in this qualitative study. Ten semi-structured focus group interviews were conducted. Two experienced moderators facilitated all focus groups, which were audio-recorded and transcribed verbatim. Strategies to ensure trustworthiness of the data were employed throughout the study. Two team members independently performed inductive conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Caregivers also discussed the role that their own attitudes toward fruits and vegetables and the knowledge of the benefits of consumption of fruits and vegetables can have in offering fruits and vegetables to their family. These results are consistent with previously conducted studies with parents of preschool-age children [46,47] which concluded that barriers to fruit and vegetable consumption among children include availability, cost, role modeling, time limitations, and knowledge of preparation.…”
Section: Discussionsupporting
confidence: 92%
“…Caregivers also discussed the role that their own attitudes toward fruits and vegetables and the knowledge of the benefits of consumption of fruits and vegetables can have in offering fruits and vegetables to their family. These results are consistent with previously conducted studies with parents of preschool-age children [46,47] which concluded that barriers to fruit and vegetable consumption among children include availability, cost, role modeling, time limitations, and knowledge of preparation.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to other studies where obesity was not reduced despite diet and nutrition education interventions improved knowledge and healthy diet [29]- [31]. For all these changes, institutional support through educational management, rules and regulations related to the school food program, the intake of high-caloric density snacks during recess in kiosks [32] and other food intake in school activities should be established, in consensus with parents and caregivers [33].…”
Section: Discussionsupporting
confidence: 64%
“…Parents, particularly mothers, hold an important role in child feeding, role modelling for healthy eating and active living, and the prevention of overweight [ 5 11 ]. Many potential strategies in tackling overweight will involve working with families, especially the primary carers of young children.…”
Section: Introductionmentioning
confidence: 99%